Predicting peak performance of a cricket player using machine learning and data analytics - Azam, Akif; Ashraf, Tarif; Asad, Ahmad Al; Anwar, Kazi Nishat; Chowdhury, Ilhum Zia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.